2005
DOI: 10.1080/05698190590903114
|View full text |Cite
|
Sign up to set email alerts
|

On the Microcontact Mechanism of Thermosonic Wire Bonding in Microelectronics: Saturation of Interfacial Phenomena

Abstract: Thermosonic ball bonding is widely used in interconnections to integrated circuits. This work used a thermosonic bonding machine and a shear tester to study the effects of preload, preheat temperature, ultrasonic power, welding time, and wire diameters on shear force. The results reveal that shear force of thermosonic wire bonding can be elucidated from the viewpoint of interfacial microcontact phenomena such as energy intensity, interfacial temperature, and real contact area. As the energy intensity is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This process is achieved using an applied pressure at an elevated temperature usually in the range of 0.5-0.8T m , where T m is the absolute melting point of the material being joined. Cold welding [24], wire bonding [25], soldering, brazing, and welding [26] also use diffusion mechanisms. Polymer-to-polymer adhesion generally occurs through the inter-diffusion of molecules in the adhesive and the adherend [27,28].…”
Section: General Adhesion Mechanismsmentioning
confidence: 99%
“…This process is achieved using an applied pressure at an elevated temperature usually in the range of 0.5-0.8T m , where T m is the absolute melting point of the material being joined. Cold welding [24], wire bonding [25], soldering, brazing, and welding [26] also use diffusion mechanisms. Polymer-to-polymer adhesion generally occurs through the inter-diffusion of molecules in the adhesive and the adherend [27,28].…”
Section: General Adhesion Mechanismsmentioning
confidence: 99%
“…Jeng and Lin (2003) extended the original CEB friction model and developed frictional energy intensity to explain the influences of thermosonic wire bonding parameters to the ball shear test results. Jeng and Chen (2005) used frictional energy intensity calculations developed from CEB friction model to study the influences of wire diameter used during thermosonic wire bonding. Jeng and Horng (2001) used micro-contact mechanism and frictional energy intensity to study the ultrasonic wedge bonding process.…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al (CEB model) [22] suggested an elastic-plastic microcontact model based on the volume conservation of plastically deformed asperities. The transition from an elastic to a fully plastic flow of the asperity is not modelled in the CEB model while the Zhao model [23] takes into account this point, and some papers [8,24] adopt the Zhao model to analyse the microcontact phenomena of thermosonic bonding. Ding et al [25,26] further suggest that the shear stress from ultrasonic vibration should be taken into account when calculating the real contact area.…”
Section: Calculation Methods Of Real Contact Areamentioning
confidence: 99%